A gamma34.5 mutant of herpes simplex 1 causes severe inflammation in the brain. - McMenamin, M; Byrnes, A; Charlton, H; Coffin, R; Latchman, D; Wood, M (1998)
A number of viral vectors are currently being evaluated as potential gene therapy vectors for gene delivery to the brain. As well as evaluating their ability to express a transgene for extended periods of time it is also essential to examine any cytotoxic immune response to such vectors as this may not only limit transgene expression but also cause irreparable harm. This work describes the effect of inoculating a gamma34.5 mutant of herpes simplex type 1 (1716lacZ) into the brain of different strains of rats and mice. Animals were monitored for weight loss and signs of illness, and their brains were evaluated for inflammation, beta-galactosidase expression and recoverable infectious virus. We report that there is (i) a powerful immune response consisting of an early non-specific phase and a later presumably T-cell-mediated phase; (ii) significant weight loss in some animals strains accompanied by severe signs of clinical illness and (iii) transient reporter gene expression in all animal strains examined. To be useful for gene therapy we suggest this virus requires further modification, it should be tested in several animal strains and the dose of virus used may be critical in order to limit damage.